1987
DOI: 10.1071/sr9870155
|View full text |Cite
|
Sign up to set email alerts
|

The dispersal of automotive lead from metropolitan Adelaide into adjacent rural areas

Abstract: About 600 surface samples and key horizons of 240 soil profiles from a 90 x 20 km study area extending from the metropolitan area of Adelaide, South Australia, to its rural hinterland, were analysed for lead. Atmospheric fallout was collected monthly at 19 locations for 2 years, and up to 3 years at fewer sites in the same area. Lead in atmospheric fallout showed little year-to-year variation and tended to be seasonally controlled with highest values in winter. Collection of lead in fallout was unaffected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Australia (Gulson et al 1981;Tiller et al 1987), Canada (Franzin et al 1979), Europe (Alcamo et al 1992), China ) and the Middle East (Erel et al 1997). An investigation of topsoil metals in a subcatchment of Sydney estuary (Homebush Bay) indicated 48%, 44% and 76% of surface Cu, Pb and Zn, respectively were attributable to atmospheric deposition (Hodge 2002).…”
Section: Atmospheric Influencementioning
confidence: 99%
“…Australia (Gulson et al 1981;Tiller et al 1987), Canada (Franzin et al 1979), Europe (Alcamo et al 1992), China ) and the Middle East (Erel et al 1997). An investigation of topsoil metals in a subcatchment of Sydney estuary (Homebush Bay) indicated 48%, 44% and 76% of surface Cu, Pb and Zn, respectively were attributable to atmospheric deposition (Hodge 2002).…”
Section: Atmospheric Influencementioning
confidence: 99%
“…At Boolaroo, it was suspected that high Pb and Cu transfer coefficients were a combined result of elevated topsoil metal concentrations (363 mg kg −1 for Pb and 223 mg kg −1 for Cu) and adsorption of atmospheric metal deposits in vegetables from the nearby smelter. Tiller et al (1987) reported that soil could be contaminated with heavy metals by aerial deposition for up to hundreds of kilometres away from the source. At Port Kembla, high concentrations of Cu in the topsoil (mean = 1032 mg kg −1 ) are likely to have resulted in greater vegetable uptake.…”
Section: Soil-plant Transfer Coefficientsmentioning
confidence: 99%
“…Merry and Tiller (1991) concluded from the Cd contents of rainfall samples that the atmospheric deposition of Cd from the Adelaide metropolitan area onto land about 20 km downwind from the urban fringe is about 3 gha-1 yr-1 • In earlier studies Tiller et al (1987) found that accessions of automotive Pb to agricultural soils east of Adelaide varied from 20mgPbkm-2 yr-1 within 20km of the city tapering off to about 2mgPbkm-2 yr-1 at distances in excess of 40km from the city. Beyond 40km downwind from the metropolitan boundary, deposition of urban contaminants was found to be indistinguishable from background concentrations.…”
Section: Atmospheric Depositionmentioning
confidence: 96%